PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN, PERTUMBUHAN PERUSAHAAN, DAN NILAI PASAR PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saputra, Randi; Efni, Yulia; Savitri, Enni (Jurnal Tepak Manajemen Bisnis, 2018)
The purpose of this study was to analyze the Influence of IntellectualCapital on the Financial Performance, Growth Company, and Market Value onCompany Property and Real Estate listed on the Indonesia Stock Exchange. Thestudy population was companies the Property and Real Estate listed in IndonesiaStock Exchange from 2011 until 2015, samples were selected using methodpurposive sampling and obtained a sample of 27 company. The data analysistechnique used is Partial Least Square (PLS). Results from the study showed thatthe of Intellectual Capital effect on Financial Performance, Growth Company,and Market Value. Financial Performance effect on Market value and IntellectualCapital affect the Market Value via Financial Performance in the companyProperty and Real Estate listed on the Indonesia Stock Exchange. GrowthCompany does not affect the Market Value and of Intellectual Capital does notaffect the Market Value through Growth Company in Company Property and RealEstate listed on the Indonesia Stock Exchange.